(3JGQjN eOjfI OeTbs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3GdMGaX GdHQRGdi s)
(3BNQgG (B:s
(3JQLeI eMeO GOQjS GdTGaYi s
(3LRA BNQ eVWQH GdChQGb Edi eMeO Hf EOQjS GdTGaYis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B331 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B81 s
Keywords: (3GdJGQjNs